2014
DOI: 10.1039/c4cp01382d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen interactions with intrinsic point defects in hydrogen permeation barrier of α-Al2O3: a first-principles study

Abstract: It is crucial to understand hydrogen interactions with intrinsic point defects in the hydrogen permeation barrier (HPB) of α-Al2O3, finding underlying reasons for the not-so-low H-permeability of the barrier, and thereby produce samples with tailored defects for optimal performance. Using density functional theory (DFT), the formation energies of intrinsic point defects in an α-Al2O3 lattice, including extrinsic H-related defects (H(i), V(Al)-H complex, HO(i) and H(O)), in all possible charged states, are firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 27 publications
13
49
1
Order By: Relevance
“…We found that H i is an amphoteric defect with the defect transition level at ε(+1/−1) = 4.19 eV, as shown in Fig. 1, in agreement with the previous work [17]. Furthermore, we investigated the other feasible forms of H defect and found that H could substitute for the O site forming H O defect with two defect transition levels at ε(+1/0) = 5.67 eV and ε(0/−1) = 6.46 eV.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…We found that H i is an amphoteric defect with the defect transition level at ε(+1/−1) = 4.19 eV, as shown in Fig. 1, in agreement with the previous work [17]. Furthermore, we investigated the other feasible forms of H defect and found that H could substitute for the O site forming H O defect with two defect transition levels at ε(+1/0) = 5.67 eV and ε(0/−1) = 6.46 eV.…”
Section: Resultssupporting
confidence: 93%
“…We found that H i could hop from one site to another site in a crystal with the migration barrier of ∼0.84 eV, which can be converted to the temperature of ∼400 K [51]. This agrees well with a previous theoretical work [17]. For V Al defect, we found that the migration barrier is much higher at ∼1.7 eV, meaning that V Al starts to be mobile at a temperature of ∼800 K [51].…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations